Efficacy of catheter ablation for premature ventricular contractions in arrhythmogenic right ventricular cardiomyopathy. (14th April 2021) - Assis, Fabrizio R.; Sharma, Apurva; Daimee, Usama A.; Murray, Brittney; Tichnell, Crystal; Agafonova, Julia; James, Cynthia A.; Calkins, Hugh; Tandri, Harikrishna
Abstract: Background: Premature ventricular contractions (PVCs) may be found in any stage of arrhythmogenic right ventricular cardiomyopathy (ARVC) and have been associated with the risk of sustained ventricular tachycardia (VT). Objective: To investigate the role of PVC ablation in ARVC patients. Methods: We studied consecutive ARVC patients who underwent PVC ablation due to symptomatic high PVC burden. Mean daily PVC burden and antiarrhythmic drug (AAD) use were assessed before and after the procedure. Complete long‐term success was defined as more than 80% reduction in PVC burden off of membrane‐active AADs. Results: Eight patients (37 ± 15 years; 4 males) underwent PVC ablation. The mean daily PVC burden before ablation ranged from 5.4% to 24.8%. A total of 7 (87.5%) patients underwent epicardial ablation. Complete acute elimination of PVCs was achieved in 4 (50%) patients (no complications). The mean daily PVC burden variation ranged from an 87% reduction to a 26% increase after the procedure. Over a median follow‐up of 345 days (range: 182–3004 days), only one (12.5%) patient presented complete long‐term success, and 6 (75%) patients either maintained or increased the need for Class I or Class III AADs. A total of 2 (25%) patients experienced sustained VT for the first time following the ablation procedure, requiring repeat ablation. No death or heart transplantation occurred. Conclusion: PVC ablation was not associated with a consistent reduction of the PVC burden in ARVC patients with symptomatic, frequent PVCs. PVC ablation may be reserved for highly symptomatic patients who failed AADs. Additional investigation is required to improve the efficacy of PVC ablation in ARVC patients.